2001
DOI: 10.1016/s0896-6273(01)00324-5
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in S6 Coupled to the Opening of Cyclic Nucleotide-Gated Channels

Abstract: In cyclic nucleotide-gated channels (CNG), direct binding of cyclic nucleotides in the carboxy-terminal region is allosterically coupled to opening of the pore. A CNG1 channel pore was probed using site-directed cysteine substitution to elucidate conformational changes associated with channel opening. The effects of cysteine modification on permeation suggest a structural homology between CNG and KcsA pores. We found that intersubunit disulfide bonds form spontaneously between S399C residues in the helix bundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
141
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 42 publications
(4 reference statements)
15
141
1
1
Order By: Relevance
“…It should also be noted that the closed-state modification rates at the three BK pore-lining sites are approximately two orders higher than that of the Shaker channels (23). These rates are even several fold higher than that of closed cyclic nucleotide-gated channels (38), the ion perme- ation gate of which has been determined to be in the selectivity filter region (38,39). In accord with previous results that small molecules such as quaternary ammonium blockers may pass in and out of the BK inner pore in both open and closed states (17,20), this observation suggests that any constriction at the cytosolic end of BK S6 does not prevent access of molecules to the inner pore and thus is unlikely to form an ion permeation gate.…”
Section: Discussionmentioning
confidence: 97%
“…It should also be noted that the closed-state modification rates at the three BK pore-lining sites are approximately two orders higher than that of the Shaker channels (23). These rates are even several fold higher than that of closed cyclic nucleotide-gated channels (38), the ion perme- ation gate of which has been determined to be in the selectivity filter region (38,39). In accord with previous results that small molecules such as quaternary ammonium blockers may pass in and out of the BK inner pore in both open and closed states (17,20), this observation suggests that any constriction at the cytosolic end of BK S6 does not prevent access of molecules to the inner pore and thus is unlikely to form an ion permeation gate.…”
Section: Discussionmentioning
confidence: 97%
“…For example, studies using intracellularly applied molecules that block the permeation pathway of CNG channels, such as divalent ions (18), tetracaine (19,20), or quaternary ammonium ions (21), have shown that blockade is not state-dependent, as if these molecules can access the pore in both open and closed channels, which is in stark contrast with the blockade properties observed in K V channels (10,11,14,(22)(23)(24). In addition, experiments examining the state dependence of cysteine modification by intracellular application of methanethiosulfonate (MTS) reagents have failed to show dramatic differences between open and closed states in the inner-vestibule region (21,25,26), results that are inconsistent with an intracellular gate in TM6, as shown in K V channels (12,15).Several studies indicate that the pore region of CNG channels plays a role in gating. For example, accessibility of cysteine reagents applied from the intracellular (27, 28) and the extracellular (27-29) side of the channel to cysteines substituted along the entire P region have shown that modification of some residues in this region perturbed normal gating by cGMP.…”
mentioning
confidence: 96%
“…For many ion channel proteins, the portion of the protein that detects the activating signal (46 -50) or acts as the activation gate (51-54) may be as large as an entire TM domain consisting of several turns of an ā£-helix (55,56). The gate of Shaker-type channels has been studied by comparing atomic structures of the closed state of the KcsA channel with the open state of the calciumactivated MthK channel (57,58).…”
mentioning
confidence: 99%